The effects of social pensions on monetary and time transfers among the poor - Olivera, Javier; Iparraguirre, Yadiraah (Pontificia Universidad Católica del Perú. Departamento de Economía, 2026)
We study the effects of Peru’s social pension program, Pension 65, on family transfers of money and time. The program provides pensions to individuals aged 65 and over who are officially classified as extremely poor and who do not receive other pensions. We use survey data matched to the program’s administrative registers and exploit the discontinuity around the welfare index that determines eligibility to estimate the intention-to-treat effects of the program on family transfers. We find that Pension 65 reduces monetary family transfers by 70% (the effect is 97% for men). There is a substantial increase in childcare hours among men, from 1 to 7 hours per week. This result is consistent with an increase in the number of young children in the household and with a reduction in time spent on leisure activities among men.
Keywords: Social pensions; Family transfers; Time use; Poverty; Ageing; https://purl.org/pe-repo/ocde/ford#5.02.01